Alveolar bone defect regeneration after bilateral periapical cyst removal with and without use of platelet rich fibrin – A case report - Vuković, Nemanja; Marjanović, Marjan; Jovičić, Bojan; Aleksić, Ema; Kalevski, Katarina; Borotić, Nenad; Pejanović, Djordje; Andjelković, Marko (Vojnosanitetski pregled, 2017)
Introduction. Periapical inflammatory lesions are local bone responses around the apex of a tooth that occur after necrosis of the pulp tissue. The ultimate goal of reconstructive surgical techniques in the treatment of the intra-bone defects is a regeneration of lost bone tissue. The aim of this report was to evaluate clinical and radiographic outcome following the removal of two big, periapical lesions, approximately of the same size, located around maxillary lateral incisors, in the same person at the same time, using two different regenerative approaches. Case report. A healthy, 21-year-old female presented with two large periapical lesions around both upper lateral incisors, and a surgical treatment was indicated. One residual defect (tooth #12) was filled with the mixture of bovine-derived hydroxyapatite xenograft and platelet rich fibrin (PRF) gel and covered with PRF membrane, while the other (tooth #22) was filled with bovine-derived hydroxyapatite xenograft only and covered with a resorbable collagen membrane. Clinical and radiographic examinations were performed seven months after the surgery. All clinical and radiographic parameters were significantly improved after the treatment on both sites; however, a newly formed bone around the tooth 12 showed a higher bone density. Conclusion. The use of PRF significantly speeded up filling of the defect compared to bovine-derived hydroxyapatite xenograft.
Keywords: oral surgical procedures; platelet rich plasma; bone regeneration